Determination of balance, fall risk, and kinesiophobia in individuals with Alzheimer’s Dementia - Doğancı, Oğuzhan; Sertel, Meral (Frontiers in Psychology, 2025)
ObjectiveThis study aimed to determine balance, fall risk, and kinesiophobia in individuals with Alzheimer’s Dementia (AD).MethodsThe study was completed with 18 AD and 18 healthy AD-free control group with early or moderate-stage AD diagnosed by a neurologist. Socio-demographic characteristics of the individuals were assessed using an evaluation form, and their balance was evaluated using the Tinetti Balance and Gait Assessment Test, Timed Up and Go Test, and Single Leg Standing Test. The Falls Risk Self-Assessment Scale (FRSAS) was used to assess the risk of falls. Kinesiophobia was assessed using the Tampa Scale for Kinesiophobia (TKS). Additionally, participants underwent the Mini-Mental State Examination (MMSE).ResultThe mean age of individuals with AD was lower than that of healthy individuals, with means of 69 ± 3.66 years and 65.4 ± 4.10 years, respectively (p = 0.012). The Tinetti balance (p = 0.005), Tinetti gait (p < 0.001), Tinetti total (p < 0.001), and the Mini-Mental State Examination (MMSE) (p < 0,001) scores were lower in AD individuals relative to controls. The FRSAS (p < 0.001) scores were higher in AD individuals relative to controls. The TKS scores were found to be similar between individuals with AD and the control group (p = 0.860).ConclusionIt was found that individuals with Alzheimer’s disease (AD) have poorer balance and a higher risk of falls compared to healthy individuals. In light of these results, balance assessments should be included when developing rehabilitation protocols for individuals with AD. Treatment protocols designed for this patient group must incorporate balance-specific exercise and training programs. Additionally, individual and environmental preventive measures should be implemented to reduce the risk of falls in individuals with AD.Clinical trial registrationClinical Trial Number: NCT05201768.